PERANAN PT SEMEN BATURAJA (PERSERO) TBK PADA MASYARAKAT DESA PUSAR KECAMATAN BATURAJA BARAT KABUPATEN OGAN KOMERING ULU TAHUN 2013-2018 - Tri Lestari, Jessy (Jurusan Sejarah Fakultas Ilmu Sosial Universitas Negeri Semarang, 2020)
This research was titled “The Role of PT Semen Baturaja (Persero) Tbk in Pusar Village Community, West Baturaja Sub-district, Ogan Komering Ulu Regency 2013-2018. The problems in this research are: how’s the activity of PT Semen Baturaja (Persero) Tbk and what is the role of PT Semen Baturaja (Persero) Tbk in Pusar Village Community, West Baturaja Sub-district, Ogan Komering Ulu Regency in 2013-2018. The methodology used in this study is a historical method with steps: heuristics, source critic, data interpretation, interviews, and historiography. In this study using a multidimensional approach with a variety of social sciences, namely: sociology and economics. Based on the results of the study, it was found that PT Semen Baturaja (Persero) Tbk is one of the State-Owned Corporate that manage natural resources in the Ogan Komering Ulu Regency not only focused on industrial activities but also conducted Social Responsibility and Programs Partnership and Community Development. With this program, it will influence the social and economic life of the community around it, especially Pusar Village. Pusar village is the most important area of ​​the corporate's production activities because the limestone and clay mining areas used as raw materials for cement production are in the Pusar Village area. Keywords: Semen Baturaja, Social, Economic, Community.